Surgical Repair of Late Complications in Patients Having Undergone Primary Hypospadias Repair during Childhood: A New Perspective - Guido Barbagli; Salvatore Sansalone; Rados Djinovic; Massimo Lazzeri (Advances in Urology)
Background. The repair of complications in patients who had undergone hypospadias repair is still an open problem. Patients and Methods. We conducted a retrospective study of patients treated for late complications after hypospadias repair. Study inclusion criteria were patients presenting urethral, corpora cavernosa deformity, and/or penile defects due to previous hypospadias repair. Exclusion criteria were precancerous or malignant lesions and incomplete data on personal medical charts. Preoperative evaluation included clinical history, physical examination, urine culture, residual urine measurement, uroflowmetry, urethrography, urethral sonography, and urethroscopy. The patients were classified into four different groups. Success was defined as a normal functional urethra, with apical meatus, no residual penile curvature or esthetic deformity of the genitalia. Results. A total of 1,176 patients were entered in our survey. Out of the 1,176 patients, 301 patients (25.5%) underwent urethroplasty (group 1), 60 (5.2%) corporoplasty (group 2), 166 (14.1%) urethroplasty and corporoplasty (group 3), and 649 (55.2%) complex genitalia resurfacing (group 4). Mean followup was 60.4 months. Out of the 1,176 cases, 1,036 (88.1%) were considered successful and 140 (11.9%) failures. Conclusion. The majority of patients (55.2%) with failed hypospadias repair require surgical reconstruction to fully resurfacing the glans and penile shaft.